Global Research Trends on Communication Practices among International Nurses in Multicultural Healthcare Settings: A Bibliometric Analysis - Acep Yudi Wahyudi; Elsye Maria Rosa (GLOBAL HEALTH SCIENCE GROUP, 2026)
The mobility of nurses across borders continues to increase, reinforcing cultural and linguistic diversity in healthcare settings. International nurse communication practices are crucial for ensuring patient safety, team coordination, and effective therapeutic relationships. Although publications on communication among international nurses in multicultural settings are growing, the global knowledge landscape remains fragmented and has not been comprehensively mapped through bibliometric approaches. Objective to map publication performance, geographic contributions, and the dynamics of research themes related to communication practices in international nurses in multicultural healthcare environments. A bibliometric study was conducted using the Scopus database (Elsevier) with publication coverage spanning 1994–2025. The search strategy combined keywords representing international or migrant nurses, clinical and interprofessional communication practices, and multicultural or cross-cultural contexts in the Title–Abstract–Keywords columns. The documents analyzed were limited to articles and reviews according to the Population, Concept, Context (PCC) criteria, resulting in 38 documents for mapping. Keyword co-occurrence mapping, overlay maps, and density maps were performed using VOSviewer. Publications showed a long period of sporadic productivity, then increased sharply in the most recent period with a peak in 2025. The co-occurrence map places general and population terms as central nodes such as article, human, nursing, adult, male, and female, with major theme clusters reflecting strengthening of cross-cultural education and competency in nursing, dimensions of psychology and interpersonal communication, and increased attention to measurement aspects and methodological rigor through questionnaires, psychometrics, and repeatability of results. The overlay map indicates a shift from an initial focus on organizational context and service quality to strengthening the theme of cross-cultural communication education, then evolving towards standardization and validation of measurements, including cross-cultural comparisons and language issues. The density map highlights the largest hotspots in the general terms population and nursing that are networked with interpersonal communication, cultural factors, and the theme of measurement and quality of evidence. Research on international nurse communication practices in multicultural healthcare has shown a strengthening trend in the recent period, with published contributions still concentrated in countries with established research ecosystems. The thematic landscape confirms that communication is understood as part of cross-cultural competence and the safety of clinical collaboration, while also moving towards the need for more valid and replicable measurements.